The Montreux years [compact disc] - Muddy Waters, 1915-1983 (BMG, 2021)
The magnificent and incomparable Muddy Waters performed three legendary concerts at the Montreux Jazz Festival throughout the 1970s. Each of these historic concerts were recorded. Muddy Waters name is synonymous with the authenticity, excellence and individuality of the festival and this collection is a celebration of his unique talent. This collection will bring together for the first time, some of the finest moments from Muddy Waters' celebrated performances alongside rare material, unheard since the original recording. Expertly curated by the Montreux Jazz Festival and BMG, restored and remastered in superlative HD audio.